Dairy foods intake and risk of Parkinson's disease: a dose-response meta-analysis of prospective cohort studies - Jiang, Wenjie; Ju, Chuanxia; Jiang, Hong; Zhang, Dongfeng (European journal of epidemiology, 2014)
Dairy foods have been linked to Parkinson's disease (PD), and a meta-analysis of prospective cohort studies on dairy foods intake and PD risk was conducted. Eligible studies were identified in a literature search of EMBASE and PubMed up to April 2014. Seven results from prospective studies were included, including 1,083 PD cases among 304,193 subjects. The combined risk of PD for highest vs. lowest level of dairy foods intake was 1.40 (1.20-1.63) overall, 1.66 (1.29-2.14) for men and 1.15 (0.85-1.56) for women. For highest vs. lowest level, the PD risk was 1.45 (1.23-1.73) for milk, 1.26 (0.99-1.60) for cheese, 0.95 (0.76-1.20) for yogurt and 0.76 (0.51-1.13) for butter. The linear dose-response relationship showed that PD risk increased by 17 % [1.17 (1.06-1.30)] for every 200 g/day increment in milk intake (Pfor non-linearity = 0.22), and 13 % [1.13 (0.91-1.40)] for every 10 g/day increment in cheese intake (P for non-linearity = 0.39). The absolute risk differences were estimated to be 2-4 PD cases per 100,000 person-years for every 200 g/day increment in milk intake, and 1-3 PD cases per 100,000 person-years for every 10 g/day increment in cheese intake. Dairy foods (milk, cheese) might be positively associated with increased risk of PD, especially for men.